(Dis)Connected Rail: Infrastructural Suspension and Phatic Politics in Romania. Issue 2 (1st December 2020) - Deoancă, Adrian
Abstract: The political force of infrastructures is often attributed to their functioning as designed, while their political afterlives remain underexplored. In this article, I explore ethnographically the phatic force of ruins of infrastructure, by dwelling on a liminal railroad segment in Romania that remains unrehabilitated many years after its breakdown. Such an open-ended state of suspension allows the isolation of infrastructure's political and affective dimensions. The Giurgiu- Bucharest railroad met its demise in 2005 in the wake of heavy floods, producing an infrastructural gap that impacts local mobility and unravels the postsocialist social contract. State authorities and citizens engage in tactics of remediation that, while unsuccessful in resuming traffic, maintain a sense of phatic connection that kindles nostalgia for the past and frustrates anticipation of the future. These tactics make the railroad a medium for hope and at the same time a symbol for the absolute impossibility of hope.